If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(7w + -5) + 4w = 2(w + 2) Reorder the terms: -2(-5 + 7w) + 4w = 2(w + 2) (-5 * -2 + 7w * -2) + 4w = 2(w + 2) (10 + -14w) + 4w = 2(w + 2) Combine like terms: -14w + 4w = -10w 10 + -10w = 2(w + 2) Reorder the terms: 10 + -10w = 2(2 + w) 10 + -10w = (2 * 2 + w * 2) 10 + -10w = (4 + 2w) Solving 10 + -10w = 4 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. 10 + -10w + -2w = 4 + 2w + -2w Combine like terms: -10w + -2w = -12w 10 + -12w = 4 + 2w + -2w Combine like terms: 2w + -2w = 0 10 + -12w = 4 + 0 10 + -12w = 4 Add '-10' to each side of the equation. 10 + -10 + -12w = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -12w = 4 + -10 -12w = 4 + -10 Combine like terms: 4 + -10 = -6 -12w = -6 Divide each side by '-12'. w = 0.5 Simplifying w = 0.5
| 48x^2=0 | | -4-5x=8-4x | | 81+5y=-4y | | 2(6t+1)-4(t-1)= | | M^2-13m+26= | | 1/4-1/5= | | 10+9x=98-x | | 7+c=40 | | (c+4)(c-3)+6(1+c^2)=(c-2)(c+2) | | 213-4x=32x+21 | | 1/5(3x+12)=3(1-4x)+12 | | -x+4=5x+22 | | 2k+1=4 | | 6x+14=-51-7 | | c=0.10x+6 | | k(2.2)+k(1.8)+5=15 | | 12x=x/3 | | 6x+10=10x+2+5+1 | | 1/3(x+3)=1/6(2x+6) | | 6x+10=10x | | x+7/4=2x-7/4 | | 6x+7=3+8x-6 | | 22p-72=16-22p | | 11x-7x=-2 | | 3-6=2 | | x(3x)-5x=2 | | 5(y-3)=5-3y | | -(2x-1)=-5(2x+9) | | 1/8(x+8)=1/24(3x+24) | | 3x+5/4=4x-5/4 | | 3x-5(2x-1)=2(4x+7) | | g(2)=x^2-x |